CONSUMER BUYING PATTERNS FOR PERSONAL CARE FMCG PRODUCTS: A CASE STUDY OF SALEM TOWN - T. Ravisankar; P. Arunachalam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today’s competitive marketplace, consumers hold a dominant position as key decision-makers. The buying behaviour of Indian consumers has significantly evolved, especially in the context of the organized retail sector. Rapid shifts in consumer preferences are being driven by occupational changes, greater media exposure, and increased urbanization. Modern consumers prefer shopping, dining, and entertainment to be integrated under one roof, reflecting a desire for convenience and a holistic experience. With rising disposable incomes, consumers now face an abundance of choices across new product categories and shopping formats. They actively seek information before making purchases, aiming for informed decisions. Shopping has transformed from a routine task into an enjoyable and engaging activity. As consumer expectations rise, the Indian retail landscape is undergoing a dynamic transformation, requiring retailers to adapt by developing effective strategies that add value to the consumer experience. Retailers must assess both the driving forces and barriers in the marketplace. This includes identifying key growth drivers, understanding consumer demographics and expectations, and analysing the competitive environment. As a result, studying consumer behaviour has become a priority for retailers aiming to better meet the needs of their target audiences. This study specifically examines consumer behaviour towards select Fast-Moving Consumer Goods (FMCGs) in Erode town, with a focus on personal care products. Given the increasing number of companies and the growing variety of products available, it is essential for FMCG firms to closely study consumer behaviour. The research aims to understand consumer actions and attitudes at different stages—before, during, and after purchase—and to identify the key factors influencing their buying decisions in the personal care segment.